The profile of skin cancer patients at Dr Pirngadi Hospital Medan: A retrospective study - Lingga, Febrina Dewi Pratiwi; Indira, Aisya; Siregar, Remenda (UI Scholars Hub, 2025)
Background: Skin cancer is among the most common malignancies, including basal cell carcinoma (BCC), squamous cell carcinoma (SCC), and malignant melanoma. In Indonesia, it ranks third after cervical and breast cancer. This study aimed to analyze the demographic, clinical, and treatment patterns of skin cancer cases at Dr. Pirngadi General Hospital, Medan, Indonesia from 2019 to 2023. Methods: A retrospective descriptive study was conducted using medical record data of all skin cancer patients treated from 2019 to 2023. Variables analyzed included age, sex, occupation, lesion site, skin cancer type, and treatment modality. Data were analyzed using univariate statistics and presented as frequency distributions. Results: A total of 106 patients were included, most aged >50 years (73.6%) and male (60.4%). Outdoor occupations, such as farming (23.6%) and entrepreneurship (23.6%), were the most common. Lesions were predominantly located on the face (93.4%). BCC was the most frequent type (90.6%), followed by SCC (7.5%) and melanoma (1.9%). Excisional surgery was the main treatment (51.9%), followed by excision with skin flap reconstruction (48.1%). Conclusion: Skin cancer in this study was most prevalent among older males with outdoor occupations, with the face being the most frequent lesion site. BCC was the predominant type, and excisional surgery remained the primary treatment. These findings provide an updated epidemiological overview to support prevention and early detection efforts in Indonesia.